2003
DOI: 10.1002/ijc.11333
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity in serial plasma DNA samples during follow‐up of women with breast cancer

Abstract: We evaluated the potential utility of occult circulating tumor DNA as a molecular marker of disease in subjects previously diagnosed with breast cancer. Using 24 microsatellite markers located at sites of frequent loss of heterozygosity (LOH) or allele imbalance in breast cancer, we analyzed DNA from 16 primary tumors (Stage IIA or more advanced) and 30 longitudinally collected plasma specimens. Clinical data at the time of plasma collection were obtained. All 16 tumors were characterized by an individual patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…The matched plasma from this sample was negative for p53 mutations using the mutation load assay. Several reports observed concordance between mutations in serum/plasma DNA and tumors (56)(57)(58)(59), whereas other reports noted inconsistency between matched samples (28,43,44,60). The lack of detection of codon 248 p53 mutation in the matched plasma DNA sample could be due to cycling of p53-mutated DNA or presence of p53-mutated DNA only a certain period after exposure.…”
Section: Discussionmentioning
confidence: 97%
“…The matched plasma from this sample was negative for p53 mutations using the mutation load assay. Several reports observed concordance between mutations in serum/plasma DNA and tumors (56)(57)(58)(59), whereas other reports noted inconsistency between matched samples (28,43,44,60). The lack of detection of codon 248 p53 mutation in the matched plasma DNA sample could be due to cycling of p53-mutated DNA or presence of p53-mutated DNA only a certain period after exposure.…”
Section: Discussionmentioning
confidence: 97%
“…The observation that tumor-specific plasma DNA is largely diluted by normal DNA has been discussed for other tumor entities (19 -21 ). Furthermore, circulating plasma DNA was suggested not to accurately reflect the clinical status of breast tumor progression (34 ). Diehl et al (24 ) showed that the fraction of mutant APC (adenomatous polyposis coli) DNA fragments in plasma varied according to tumor stage of colorectal cancer patients, and the fraction of mutant APC fragments in plasma of patients with advanced tumors was 11% of the total APC fragments.…”
Section: Discussionmentioning
confidence: 99%
“…This has also been reported for FHIT (44), APC, and CDH1 (13). Wang et al (45) reported that nearly every breast tumor has an individual pattern of allelic imbalance or loss of heterozygosity at multiple loci, which constitutes its "fingerprint. "…”
Section: Discussionmentioning
confidence: 99%